2021
DOI: 10.1002/spe.2987
|View full text |Cite
|
Sign up to set email alerts
|

Ajalon: Simplifying the authoring of wearable cognitive assistants

Abstract: Summary Wearable Cognitive Assistance (WCA) amplifies human cognition in real time through a wearable device and low‐latency wireless access to edge computing infrastructure. It is inspired by, and broadens, the metaphor of GPS navigation tools that provide real‐time step‐by‐step guidance, with prompt error detection and correction. WCA applications are likely to be transformative in education, health care, industrial troubleshooting, manufacturing, assisted driving, and sports training. Today, WCA application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Many video annotation tools have been developed and used since 1990s, for instance in creating instructional videos [4], [29], analyzing video experiments [30], sharing comments on videos through social networks [31], and generating labeled data for training machine learning models [14]. These tools are typically used for annotation after the video has been captured.…”
Section: B Video Annotation Toolsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many video annotation tools have been developed and used since 1990s, for instance in creating instructional videos [4], [29], analyzing video experiments [30], sharing comments on videos through social networks [31], and generating labeled data for training machine learning models [14]. These tools are typically used for annotation after the video has been captured.…”
Section: B Video Annotation Toolsmentioning
confidence: 99%
“…From the interaction perspective, the mouse and keyboard were the most commonly used input devices before tablets and smartphones with touchscreen become popular. In case of annotating pre-recorded video, it is preferred to use a mouse and a keyboard to achieve precise pointing and fast typing, although users have reported that they become fatigued when using these devices to annotate lengthy video [14]. When users need to use their hands to conduct other tasks simultaneously, hands-free interaction with the annotation tool becomes an essential requirement.…”
Section: B Video Annotation Toolsmentioning
confidence: 99%
See 3 more Smart Citations